Perencanaan Strategi Pengembangan Pendidikan Islam - Naik Syaputra Kaloko (Journal on Education, 2023)
Until now aspects of educational planning in the Islamic education environment, both macro and micro, are still seen as something that is not important. Educational planning, which should be an integral part of the management of the administration of Islamic education, is often ignored and not yet a tradition in the development of Islamic education. This article offers an Islamic Education Planning Strategy, along with various possibilities and alternatives that may be carried out in developing Islamic education in the future, this article also tries to offer several alternative models of Islamic education planning, especially related to the dynamics of the community that are stakeholders of education. This article has a plan. the concepts, paradigms, strategies and steps of Islamic education planning. The expected results in this plan can formulate desired and controlled goals. The selection of the right program, to achieve the goals and collect and designated resources is always limited.